A cultural theory of populist leadership: fatalism, authoritarianism and the first Trump presidency - Verweij, Marco (Frontiers in Political Science, 2025)
This article asks whether a unified framework can integrate established traits of populist leadership, propose novel ones, and link populist leaders to their social support. To do so, it uses Mary Douglas’s cultural theory, and especially its typology of four “ways of life” (hierarchy, egalitarianism, individualism and fatalism), in combination with Jan-Werner Müller’s definition of populism (as movements with leaders who claim to be the sole representatives of a homogenous people). This theoretical approach is illustrated through a congruence analysis of Donald J. Trump’s first presidency using secondary data. The analysis finds that the fatalistic way of life encapsulates populist leadership. All features of populist rule identified in the literature—such as corruption, nepotism, and protectionism—are consistent with fatalism. The framework also highlights additional traits (for instance, secretiveness, vengeance, and conspiracy-proneness) implied by fatalism. The Trump case exemplifies these arguments: his administration’s conspiratorial rhetoric, punitive governance style and zero-sum outlook reflect a fatalistic ethos. Crucially, cultural theory bridges leaders and followers: fatalism links the supply side of populism to its demand size. Overall, Douglas’s cultural theory unifies scattered populist traits under a coherent logic and provides a bridge between populist leadership and people’s support of such leadership. This integrated approach advances theoretical understanding of populist leadership while suggesting new avenues for empirical research.